Purification And Characterization Of Organic Solvent Tolerant Protease From Pseudomonas Aeruginosa Strain K - Yusoff, NorulAiman (2007)
A bacterium known as Strain K was identified as Pseudomonas aeruginosa since it 16S rRNA sequence exhibited similarity of up to 99 % with P. aeruginosa from the NCBI database. Protease from the P. aeruginosa strain K was purified to homogeneity by 80.6 fold and 107 % recovery using a combination of ultrafiltration and ion exchange chromatography on Q-Sepharose. In second method, protease K-01 was purified to homogeneity by 116.2 fold purification and 199 % recovery, using a combination of ultrafiltration and hydrophobic interaction chromatography on Butyl-Sepharose. The purified protease was named as protease K-01. The apparent molecular mass of the purified protease K-01 was estimated to be 33 kDa on gel filtration Sephadex G-100, and SDS PAGE. The purified protease hydrolyzed azocasein at optimum temperature of 55 ºC. However, the enzyme lost its activity with a half life of more than 60 min at 55 and 60 ºC. The optimum activity of the protease was observed at pH 8.0 and it was stable in the pH range of pH 6 to 13. The protease activity was completely inhibited by EDTA and 1,10-phenantroline, while 70 and 30 % reduction of protease activity was observed in the presence of DTT and 2-mercaptoethanol respectively. Among the metal ions tested, Mg2+ and Ca2+ ions increased enzyme activity by 8 %. Protease activity was completely inhibited by Fe2+, Ni2+, Cu2+, Ag2+, Zn2+, and Hg2+ ions. Fe3+ and Co2+ ions were found to restore the activity of inactivated protease by 1mM EDTA. Protease K-01 was more stable in water miscible organic solvents (DMSO, methanol, ethanol, 2-propanol, n-butanol, and 1-decanol) than water immiscible organic solvent. For substrate specificity, protease K-01 was able to hydrolyze several native proteins such as casein, haemoglobin, albumin and gelatin.